An eficient method for automated control flow testing of programs : M.A Thesis Information Technology : 60 48 01 - Nguyễn, Quang Trung (ĐHCN, 2017)
The main goals of software testing are to reveal bugs and to ensure that the system being developed complies with the customer’s requirements. To make testing effective, it is recommended that test planning/development begin at the onset of the project. Software testing techni ques can be divided into approaches : black - box and w hite - box techniques. Black - box testing is mainly a validation technique that checks to see if the product meets the customer’s require ments. On the other hand, white - box testing is a verification technique which uses the source code to guide the selection of test data. Currently, software companies focus only on the black - box testing techniques in order to validate because White - box te sting very expensive , slow and it requires the tester have knowledge of code . In addition, implementing blac k - box and white - box testing separately make s white - box testing becomes more inefficient. This thesis presents a me thod for automated control flow testing of unit programs to sol v e the problems . The key idea o f this method is to combine the black - box and white - box techniqu es i n order to minimize the complex ity of white - box testing. Instead of per forming black - box and white - box separately, the proposed method uses the test inputs that are gener ated by black - box to reduce searching space of white - box testing. The method then continually eliminates arcs in remaining space to find non - duplicated test paths. Therefore, the pro posed method is able to operate white - box testing with less effort than the current method